SHAPING ANTIMONOPOLY LEGISLATION? THE LOBBYING OF BUSINESS ELITES IN BRAZIL - Guerra Filho, Arthur (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2021)
Abstract Many people insinuate that large corporations lobby against effective antimonopoly legislation. But what, in fact, is the evidence to support those allegations? This article collects and examines data and documents — legislative records, academic literature, documents of business associations, and press archives — about the lobby of Brazilian business elites on antitrust legislation. It aims to contribute to the academic debate by being the first academic work to comprehensively look at corporate lobbying on Brazilian antitrust bills and legislation, from the first antitrust regulations in 1938 to the current Antitrust Act of 2011. The results of the analysis show that Brazilian business organisations and their leaders have consistently monitored and tried to influence the outcome of antitrust bills and legislation. The article finds a pattern of business elites lobbying for a less interventionist antitrust legislation or the entire repeal of the antitrust legislation. The current Antitrust Act 2011 was turned less interventionist than the Act of 1994, by amendments proposed by a heavily corporate-funded senator in his electoral campaign, who worked accordingly with the lobby of the National Industry Confederation (CNI). Key words Antitrust Law. Antimonopoly. Business Elites. Lobbying. Rent-seeking. Resumo Muitas pessoas insinuam que grandes empresas fazem lobby contra legislações antimonopólio. Mas quais, de fato, são as evidências para amparar tais alegações? Este artigo coleta e examina dados e documentos — documentos legislativos, literatura acadêmica, documentos de associações empresariais e arquivos da imprensa — sobre o lobby das elites empresariais brasileiras sobre projetos de lei e legislação antitruste. O artigo tem como objetivo contribuir para o debate acadêmico ao ser o primeiro trabalho acadêmico a olhar de forma abrangente para o lobby das elites empresariais brasileira em projetos de lei e legislação antitruste, desde a primeira regulação antitruste em 1938 até a atual Lei nº 12.529/11. Os resultados da pesquisa mostram que as organizações empresariais brasileiras e seus líderes têm monitorado e tentado influenciar de maneira consistente o resultado dos projetos de lei e legislação antitruste. O artigo encontra um padrão de elites empresariais fazendo lobby por uma legislação antitruste menos intervencionista, ou mesmo a revogação total da legislação antitruste. A atual Lei nº 12.529/11 tornou-se menos intervencionista do que a Lei nº 8.884/94, por meio de emendas propostas por um senador fortemente financiado por empresas em sua campanha eleitoral, que trabalhou em consonância com o lobby da Confederação Nacional da Indústria (CNI). Palavras-chave Direito Antitruste. Antimonopólio. Elites empresariais. Lobby. Rent-seeking.